Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar Siswa Siswa Kelas V SDN 119 Sarira - Theresyam Kabanga'; Anita Bunga (LPPM UKI Toraja, 2022)
This study aims to improve learning outcomes through the application of a project based learning model for class V SDN 119 Sarira. The approach used in the research is a qualitative approach and classroom action research (CAR) which consists of 4 stages, namely planning, implementation, observation and reflection. Research subject are the fifth grade students of SDN 119 Sarira as many as 30 people consisting of 12 boys and 18 girls. The research instrument used was the teacher’s observation sheet and the student observation sheet. II increased with a completeness level of 70% with a good category. Based on the results of the researches, it can be concluded that the application of the project based learning model can improve the learning outcomes of fifth grade students at SDN 119 Sarira.